(untitled) (Journal of Mechanical Engineering, 2009)
Heat transfer in a porous medium over a stretching surface with internal heat generation and suction or injection has been analyzed numerically in the presence of radiation. In this analysis, the governing equations are transformed into a system of ordinary differential equations and solved them numerically using Nachtsheim-Swigert shooting iteration technique. The local similarity solutions for the flow and the heat transfer characteristics are presented graphically for various material parameters entering into the problem. The effects of the pertinent parameters on the local skin friction coefficient (viscous drag) and the Nusselt number (rate of heat transfer) are also displayed graphically. Keywords: Internal heat generation, suction, injection, radiation, Nusselt number. doi: 10.3329/jme.v40i1.3469 Journal of Mechanical Engineering, Vol. ME40, No. 1, June 2009 22-28